2023
DOI: 10.22359/cswhi_14_1_07
|View full text |Cite
|
Sign up to set email alerts
|

Management of Informal Caregivers’ Burden in a Selected Region of the Czech Republic

Abstract: Objective: Care of handicapped or elderly by the family members in the home environment brings not only many positives for the care recipients, but can also impose a significant burden on the caregiver. The goal of the study was to assess the caregiver burden, burnout syndrome and the effect of caregivers’ sociodemographic characteristics. Design: Cross-sectional study. Participants: The sample consisted of 168 caregivers who took care of disabled children or seniors. Methods: Zarit Burden Interview identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Research on ICs of patients with different types of diseases showed that burnout is related to lower subjective health, social support, anxiety and depression, and lower QoL in all dimensions [ 28 , 29 , 30 , 31 ]. The scores for emotional exhaustion and personal accomplishment in the informal caregiving literature stand out in comparison with the scores of depersonalization [ 31 , 32 ]. Burnout is also related to negative consequences for the care recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ICs of patients with different types of diseases showed that burnout is related to lower subjective health, social support, anxiety and depression, and lower QoL in all dimensions [ 28 , 29 , 30 , 31 ]. The scores for emotional exhaustion and personal accomplishment in the informal caregiving literature stand out in comparison with the scores of depersonalization [ 31 , 32 ]. Burnout is also related to negative consequences for the care recipient.…”
Section: Introductionmentioning
confidence: 99%